Emergent spatiotemporal dynamics of the actomyosin network in the presence of chemical gradients - Miller, Callie J (Integr Biol (Camb), 2019)
We used particle-based computer simulations to study the emergent properties of the actomyosin cytoskeleton. Our model accounted for biophysical interactions between filamentous actin and non-muscle myosin II and was motivated by recent experiments demonstrating that spatial regulation of myosin activity is required for fibroblasts responding to spatial gradients of platelet derived growth factor (PDGF) to undergo chemotaxis. Our simulations revealed the spontaneous formation of actin asters, consistent with the punctate actin structures observed in chemotacting fibroblasts. We performed a systematic analysis of model parameters to identify biochemical steps in myosin activity that significantly affect aster formation and performed simulations in which model parameter values vary spatially to investigate how the model responds to chemical gradients. Interestingly, spatial variations in motor stiffness generated time-dependent behavior of the actomyosin network, in which actin asters continued to spontaneously form and dissociate in different regions of the gradient. Our results should serve as a guide for future experimental investigations.